Digital Marketing Transformation via Social Media Utilization: Enhancing the Value Added of Micro, Small, and Medium Enterprise (MSME) Products - Achmad Faisal; Muhamad Firdaus; Muhamad Roby Yahya; Andi Lana Prasetiowati; Tasrin Tasrin; Kasmad Kasmad; Udin Ahidin (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This community service activity aims to improve the knowledge and skills of the members of PKK RW 025 Tambun Selatan in utilizing social media as a digital marketing tool for MSMEs through the practice of producing and promoting perfume products. The development of digital technology requires MSME actors to be able to utilize social media as an effective and efficient promotional medium. The implementation method of this activity was carried out through the delivery of materials, discussions, and direct practice in perfume production and digital marketing strategies. The materials provided included creating attractive product photo and video content, delivering product information such as benefits and advantages, as well as promotional techniques through social media platforms such as Instagram, WhatsApp, Facebook, and TikTok. The results of the activity showed that the participants of PKK RW 025 Tambun Selatan gained an understanding of the importance of digital marketing in business development and were able to practice product promotion strategies creatively and communicatively. In addition to improving digital marketing skills, this activity also had a positive impact on increasing participants’ creativity, self-confidence, and entrepreneurial spirit. Through this activity, it is expected that the participants of PKK RW 025 Tambun Selatan will be able to independently implement digital marketing strategies to help expand market reach and increase sales opportunities for MSME products.